The Effect of Training on Employee Performance Through the Intervening Variables of Employee Competency and Employee Work Productivity at PT Bank Negara Indonesia Karangayu Branch Office - Putri, Mutiara Kencono; Budiati, Yuli; Kuswardani, DC. (Majapahit Journal of Islamic Finance and Management, 2025)
In the banking sector, employee performance is crucial for ensuring service quality and institutional competitiveness. This study examines whether training programs at PT Bank Negara Indonesia (Persero) Tbk Karangayu Branch significantly affect employee performance and the extent to which competence and productivity mediate this relationship. It also aims to contribute theoretically by addressing prior research gaps and providing practical insights for improving training and employee development in the industry. The variables studied include training, performance, competence, and productivity within an empirical research model. Data were gathered from 65 employees of the Karangayu branch through interviews and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) to assess direct and indirect relationships. Results show that competence serves as a key mediator linking training to performance, while productivity also mediates this causal pathway. Training enhances productivity, which then boosts performance, making productivity a reinforcing intermediary that strengthens the relationship between training and performance.